Windows 10 Development with XAML and C# 7 - Liberty, Jesse (Apress, 2018)
Master XAML and C# 7 to get the most from Windows 10 with experienced authors and Microsoft MVPs - Jesse Liberty, Phil Japikse, Jon Galloway, and Jonathan Hartwell. This book begins with a nuts-and-bolts examination of how the technologies fit together and shows you everything you need to get up and running with the new platform. Once you have a good understanding of the basics, you progress to more advanced topics steadily increasing your understanding as a whole. This holistic knowledge is essential to truly master Windows 10 development. Each topic is covered clearly and concisely and is packed with the details you need to code effectively. The most important features are given a no-nonsense, in-depth treatment and chapters contain examples that demonstrate both the power and the subtlety of Windows 10. Pro Windows 10 Development with XAML and C# 7 focuses on the features that you need for your project and brings your existing C# coding knowledge to bear. You will: Discover what universal Windows 10 apps are capable of and why they are special Use advanced features to create immersive and engaging Windows 10 applications Create applications that work seamlessly on tablets and desktops Prepare and deploy your Windows 10 applications.